AB0203 Possible Role of Fractalkine/CX3CL1 (FKN) in the Microvascular Damage of Systemic Sclerosis (SSC). (9th June 2015) - Stefanantoni, K.; Sciarra, I.; Corinaldesi, C.; Caucci, M.; Vasile, M.; Iannace, N.; Saturno, M.C.; Crescioli, C.; Valesini, G.; Riccieri, V.
Abstract : Background: Systemic Sclerosis (SSc) is a severe autoimmune disease characterized by tissue fibrosis, immune dysregulation and vascular dysfunction. Nailfold Videocapillaroscopy (NVC) is a simple diagnostic tool that is commonly used to assess microvascular changes in SSc (1). Fractalkine/CX3CL1 (FKN) is a member of CX3C chemokine family and is expressed on tumor necrosis factor α (TNF-α) and IL-1 stimulated endothelial cells (2, 3). In SSc it seems to be expressed on endothelial cells in the affected skin and in lung tissue and raised serum levels of FKN are associated with higher erythrocyte sedimentation rates, presence of digital ischemia, and severity of pulmonary fibrosis (4) and pulmonary arterial hypertension (5). Objectives: To assess the role of Fractalkine/CX3CL1 in the development of the different capillaroscopic patterns in SSc. Methods: We enrolled 39 patients with SSc, diagnosed according to 2013 ACR/EULAR criteria. All patients underwent clinical, instrumental and laboratory evaluations. NVC was defined as "early", "active" and "late" patterns (1). FKN levels were assessed by Bioplex Luminex platform. Results: We found significantly higher FKN serum levels in patients with "early" and "active"capillaroscopic patterns ("non late" patterns) respect to those with "late" pattern (355.6±176.3 ng/ml vs 307.2±104.2 ng/ml; p<0.0001). Conclusions: Our results suggest that FKN, a chemokine highly expressed on activated endothelial cells, is involved in the early phases of the microvascular damage in our patients, as identified by the "early" and "active"capillaroscopic patterns. Further investigations are needed to determine if FKN may be considered as a useful biomarker, at least at the beginning of the vascular manifestations in SSc. References: Cutolo M: J Rheumatol. 2000 Jan;27(1):155-60. Fraticelli P et al: J Clin Invest 2001; 107: 1173-81 Garcia GE at al: J LeukocBiol 2000; 67: 577-84 Hasegawa M et al: Ann Rheum Dis 2005; 64: 21-8 Marasini B et al: Clinical & Developmental Immunology, December 2005; 12(4): 275-279 Disclosure of Interest: None declared